Imunoterapia com igY aviária em ratos experimentalmente infectados porTrypanosoma evansi - Sampaio, Luzia Cristina Lencioni (2014)
Trypanosoma evansi is a protozoan flagellate that affect cattle, sheep, goats, donkeys, cats and pigs. The disease is particularly important in horses, known as "Mal das Cadeiras", due to deficits characteristic of locomotion in animals infected. The disease has a worldwide distribution, with several reports of natural infections in different regions in Brazil. Several pharmaceutical drugs have been recommended for the prophylaxis and control of the parasite, but over the years, these drugs have lost their effectiveness and protozoan looks developing resistance. The production and use of avian antibodies has aroused great interest in the scientific community because of the diversity of diagnostic and therapeutic applications. Due to the phylogenetic distance, immune diversification mechanisms and transferability of serum immunoglobulin to the egg yolk, currently recognizes a number of advantages to using avian antibodies rather than antibodies of mammals. This study produced a specific immunoglobulin against Trypanosoma evansi from immunization of chickens using an isolate of the parasite. After extraction and purification from egg yolk, cytotoxicity and genotoxicity of these antibodies in cultures of human leukocytes were evaluated. The therapeutic efficacy was tested in Rattus norvegicus. The trial also assessed the use of avian antibody associated with imidocarb dipropionate and diaceturate of diminazene. The toxicity tests showed that immunoglobulin does not produce gene and cell injury. In vivo tests showed increased in longevity and pre-patent period, mainly in rats treated with avian immunoglobulin associated with pharmacological treatment. The immunization and the extraction protocol used in this study allowed obtaining specific antibodies against protozoan and innocuous to the host. Moreover, when administered for therapeutic purposes, strengthens the immune system and prolongs the survival of infected patients.